Devices and circuits [Technology 2000 analysis and forecast]. - Geppert, L. (IEEE spectrum)
In the high-profile electronics industry, a new microprocessor architecture is enough of a rarity to excite great anticipation. In the first year of the third millennium, industry watchers will have plenty to look forward to, as the first batch of high-end computers built with Intel Corp.'s new microprocessor, Itanium (formerly Merced), becomes available. This year could also mark the beginning of the end for microprocessors with clock rates below a gigahertz. Leading the attack will be the Power4 processor chip from IBM Corp. and the Alpha 21364 from Compaq Computer Corp., both slated to run at speeds of 1 GHz and higher